Ontic elements as markers of translinguality in E. Mizhit's poems - Valikova, Olga A.; Sinyachkin, Vladimir P.; Kulieva, Sheker A. (The New Research of Tuva, 2023)
The article undertakes an analysis of the poems by the Tuvan poet E. Mizhit (1961–2023), composed in the Russian language. The analysis employs an ontopoetic approach, wherein the object of inquiry is a translanguaging artistic text (crafted by the author in a non-native language), and the focus is on ontic elements facilitating the reconstruction of discrete facets within the author's indigenous linguistic worldview, specifically that of the Tuvan.Within the artistic corpus of texts, discernible ontic elements encompass “lullaby”, “Earth”, “Sky”, and “yurt”. These elements are construed as corollaries to the linguistic worldview of the Tuvan ethnic milieu, affording the Russian-speaking reader an avenue to acquaint themselves not merely with an alternative perceptual schema but also with a novel attitude grounded in distinct values, conceptions, mandates, and cultural paradigms. Immersion in the culture of the Tuvan ethnic group via poetic text constitutes an experiential emulation of alternative reader dispositions, transcending the “horizon of expectation” as dictated by the monolingual paradigm.
Keywords: translanguaging; Russian-language artistic production; Tuvan literature; Tuvan poetry; Eduard Bairovich Mizhit; ontopoetics; ontic element